Satisfacción del usuario con insuficiencia renal crónica y aplicación de principios bioéticos de la enfermera(o) - Florian Avila, Martha Melissa (2015)
This research study descriptive correlational and cross-cutting. It was performed in young adult and mature users with chronic renal failure in hemodialysis service of a hemodialysis clinic in Trujillo 2015, in order to determine the relationship between the level of user satisfaction with chronic renal failure with the application of the principles bioethical Nurse (o). The theoretical assumptions underlying the research are: Ethics (Van Der Linde, 2001), Bioethical Principles (Amaro, 2004; Beauchamp and Childress, 2002) and Satisfaction (Arteaga, 2003 and Vicuña, 2002). The sample universe consisted of 40 people who met the inclusion criteria. The information was obtained by the following instruments: perceived user satisfaction and application of bioethical principles Nurse (o), valid and reliable, applied through personal interview, taking into account the rights of anonymity, confidentiality and free participation. The results found that there was significance between the high level of user satisfaction with chronic renal failure in relation to the application of bioethical principles nurse. It was found that 70% of users with chronic renal failure are satisfied with the care provided, and 85% are satisfied with the implementation of bioethical principles.